What Would Make it Easier for Patients to Complete a Headache Diary - Alvares, Mônica Maria Costa do Rêgo; Alcantara, Raimundo Neudson Maia; França, Mário Hermes Rios; Sampaio, Rhina de Freitas; Carvalho, Pedro Rubens Araújo; Neri, Pedro Vinicius da Silva; Miná, Larissa Brenda Gonçalves; Vasconcelos, Karla Rafaele Silva; Verde, Ana Silvia Sobreira Lima; Lima, Sylvio Ricard Gonçalves de Souza; Landim, João Igor Dantas; Carvalho, Joao Jose Freitas de (Headache Medicine, 2023)
Full abstract in PDF.